Effects of long-term summer deficit irrigation on ‘Navelina’ citrus trees - Gasque, María; Martí, Pau; Granero, Beatriz; González-Altozano, Pablo (Elsevier, 2020)
The effects of long-term summer deficit irrigation (RDI) strategies on ‘Navelina’ orange trees (Citrus sinensis L. Osbeck) were assessed in a drip-irrigated commercial orchard located in Senyera (Valencia, Spain). Three irrigation treatments were applied during five consecutive years (2007–2011): a control treatment, without restriction, and two RDI treatments, in which the water reduction was applied during the summer (initial fruit enlargement phase). During the first three seasons, the trees under the control treatment received 110% of the theoretically required irrigation dose (ID), and the RDI treatments received 40% and 60% of the full ID during the deficit period. During the last two years of the study, the control treatment was irrigated at 100% of the ID and the amount of water applied in the RDI treatments was additionally decreased 20% from the reduced ID of the preceding years. The crop’s response to summer deficit irrigation was analysed in relation to tree water status, which was assessed by relying on midday stem water potential (Ψst). The lowest Ψst values were reached, as expected, at the end of the water deficit period and with the most stressed treatment. These minimum Ψst values ranged between −1.6 MPa in 2008 and −2.5 MPa in 2010. In most occasions, the trees under RDI treatments showed a fast hydric recovery and had completely re-hydrated one week after restarting irrigation. Summer RDI treatments did not cause negative effects on either the amount or on the quality of the yield if the threshold value of Ψst = −2.0 MPa was not surpassed. According to the results, it can be concluded that long-term RDI strategies may be applied successfully on Navelina orange trees during summer without negatively affecting the studied parameters while allowing water savings between 12% and 27%.